Cognitive load and decision-making in youth soccer training: Implications for player development - Sargsyan, Arman (Journal of Sports Research, 2026)
Football performance is dependent upon quick decision making, perceptual abilities, and cognition. In many youth football development programs, however, coaches fail to fully address the cognitive demands placed on players during games. This article uses principles of cognitive load theory, motor learning, and sport psychology to discuss how cognitive load affects decision-making in youth players. Different coaching practices either increase or decrease cognitive load, depending on how a coach structure activities. Tips on how coaches can achieve a desirable cognitive load are presented. Youth football coaches should strive to find the balance that allows players to achieve their maximum learning potential without overloading their working memory. Ideal cognitive load promotes quicker and smarter decision making on the field, increased confidence, and long-term player development. The purpose of this article is to explore how Cognitive Load Theory (CLT) can be applied to youth soccer instruction with the goal of expediting decision-making skills and producing more effective long-term athlete development. A conceptual/integrative review design was utilized and informed by cognitive load theory, ecological dynamics, and motor learning and skill acquisition literature. This analysis discussed how various task constraints impact working memory capacity, perception–action coupling, and schema development in youth players. However, small-sided games and constraint-led practices that are appropriately challenging allow for germane cognitive processing and the development of flexible decision-making abilities. Methodically manipulating space, numbers, rules, and the coach’s teaching behavior favors anticipation and scanning behaviors while developing efficient first-touches and reducing anxiety during game-play.